The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s12105-022-01410-3
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Grading in Intestinal-Type Sinonasal Adenocarcinoma: Tumor Budding as an Independent Prognostic Parameter

Abstract: Since sinonasal intestinal-type adenocarcinomas (ITAC) show resemblance to colorectal adenocarcinomas, we aimed to investigate novel prognostic factors of outcome, with particular focus on the role of tumor budding (TB). Retrospective clinico-pathological single-institution study on consecutive ITAC patients between 1996 and 2020. Histopathological parameters including conventional subtypes and TB features (low, intermediate, high) were evaluated with the aid of pancytokeratin (AE1/AE3) immunohistochemical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(75 reference statements)
1
4
0
Order By: Relevance
“…The second study by Meerwein et al (31 patients) was also monocentric and applied the same TB stratification. The authors concluded that TB is an independent negative prognostic marker regardless of the tumor subtype and stage [16]. Our data strengthen the evidence of an independent prognostic value of TB in ITAC and are therefore in line with previous conclusions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The second study by Meerwein et al (31 patients) was also monocentric and applied the same TB stratification. The authors concluded that TB is an independent negative prognostic marker regardless of the tumor subtype and stage [16]. Our data strengthen the evidence of an independent prognostic value of TB in ITAC and are therefore in line with previous conclusions.…”
Section: Discussionsupporting
confidence: 92%
“…So far, only two studies (for a total of 63 patients) have investigated the presence of TB in ITAC. The authors found that TB is a negative prognostic marker, similar to CRC and many HNSCCs [13,16], but their results required further validation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another morphological feature associated with worse prognosis is tumor budding, a finding described in colorectal oncologic pathology as the presence of isolated single tumor cells or small clusters of up to 5 cells in the tumor stroma. Maffeis et al and Meerwein et al found a substantial association between tumor budding and prognosis [14,15]. Thus, tumor budding might act as TDTC, but data on pre-treatment detectability are currently lacking.…”
Section: Intestinal-type Adenocarcinomamentioning
confidence: 99%
“…Tumor budding [14,15] High copy number alterations [16,17] Aneuploidy, 4q32-ter, ANXA2, DCC, H-RAS, MET, MYC, PFOU5F1B, PTP4A3, PTPN1, TIMP2, TIMP3, TP53 [6] miR-205 and miR-449 overexpression [18] Functional p53 [19][20][21] Neoadjuvant chemotherapy with cisplatin, 5-fluorouracile, and leucovorin MET mutation [26,27] MET inhibitors HRAS mutation [27] RAS or MAPK/ERK pathway inhibitors EIF2S1 and/or EIF6 upregulation [28] Anti-eukaryotic translation initiation factor agents Mutation of PIK3CA, BRCA1, IDH1, ERBB2, BRAF, KRAS, CDKN2A, NF1 [29] Use of respective targeted therapies as orbital encroachment [33,[35][36][37][38][39][40]. Recently, short-term prognosis was found to be improved in patients with sinonasal SCC undergoing neoadjuvant chemotherapy compared with the standard of care [41].…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%